Enhancement of Chlorella vulgaris Biomass Cultivated in POME Medium as Biofuel Feedstock under Mixotrophic Conditions - Nur, M.M. Azimatun; Hadiyanto, H. (ITB Journal Publisher, LPPM ITB, 2015)
Microalgae cultivated in mixotrophic conditions have received significant attention as a suitable source of biofuel feedstock, based on their high biomass and lipid productivity. POME is one of the wastewaters generated from palm oil mills, containing important nutrients that could be suitable for mixotrophic microalgae growth. The aim of this research was to identify the growth of Chlorella vulgaris cultured in POME medium under mixotrophic conditions in relation to a variety of organic carbon sources added to the POME mixture. The research was conducted with 3 different carbon sources (D-glucose, crude glycerol and NaHCO3) in 40% POME, monitored over 6 days, under an illumination of 3000 lux, and with pHÂ =Â 7. The biomass was harvested using an autoflocculation method and dry biomass was extracted using an ultrasound method in order to obtain the lipid content. The results show that C. vulgaris using D-glucose as carbon source gained a lipid productivity of 195 mg/l/d.